IMPORTANCE OF EYE MICROSURGERY IN MODERN TREATMENT (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
According to the World Health Organization, more than 2 billion people now have vision loss and related disabilities due to eye diseases. However, about 1 billion of them can be treated with surgery. Eye injuries - eye injuries from various objects (stone, sand, cement, lime, metal, wood, glass, coal, etc.). In this case, the eye hurts, tears flow a lot, and the patient cannot look at the light. This article provides information about the importance of eye microsurgery in modern treatment.